Produção de nanoestruturas de carbono para bioaplicações - Almeida, Larissa Solano de (Universidade Federal de São Carlos, 2025)
Carbon nanotubes (CNTs) stand out in research due to their attractive chemical and physical properties, which are influenced by the high quality of these nanostructures and allow their application in several areas. The quality of CNTs is directly related to growth parameters, such as gas flow, voltage, time, and temperature. Conventional techniques, such as chemical vapor deposition (CVD), produce carbon nanostructures with fewer defects but require high temperatures, reaching 1000 °C. A promising alternative is plasma-assisted chemical vapor deposition (PECVD), capable of producing CNTs at temperatures close to 450 °C. This work aimed to obtain CNTs through the PECVD technique with a pulsed DC source. The growth was performed on a nickel substrate, using Ar/H₂/CH₄ gases, with a voltage of 500 to 800 V, temperature of approximately 450 °C, and treatment times ranging from 5 to 30 minutes. The discovered nanostructures were recorded by Raman spectroscopy, SEM, TEM, XPS, fixed-sphere wear test, UV-Vis scattering test, and cytotoxicity and toxicity tests in terrestrial and aquatic environments. The Raman spectra revealed bands characteristic of carbon-based materials, such as D, G, D’, 2D, and D+G. For effective growth, the plasma needed to have sufficient energy, and the SEM micrographs confirmed the effective formation of CNTs at resistances above 700 V. The growth time directly influenced the quantity and quality of CNTs, with greater production observed in periods longer than 15 minutes. The diameter of the CNTs increased with the increase in the total gas flow. The results indicated the delivery of multi-walled carbon nanotubes (MWCNTs), with the presence of defects, which may be advantageous depending on the application. The optimized growth settings were: flow rate of 235 sccm, voltage of 800 V, and time of 30 minutes, producing MWCNTs effectively. Furthermore, with the optimized settings, it was possible to evaluate the incorporation of nitrogen on the surface of the CNTs. The results demonstrated that the increase in the nitrogen flow caused greater structural disorder, indicating its incorporation. The CNTs presented greater dispersivity in an aqueous medium compared to CNTs with nitrogen and commercial CNTs. Furthermore, the CNTs demonstrated lower toxicity in biological, terrestrial, and aquatic systems, being promising for bioapplications. As a second work proposal, the production of a CNTs/DLC hybrid carbon nanostructure was carried out, evaluating its tribological potential. The material presented wear resistance, showing significant potential due to the synergy between the properties of CNTs and DLC films. However, further studies and characterization techniques are needed to validate these results. Thus, the work highlights the importance of optimizing growth parameters to obtain quality and quantity of CNTs at low temperatures using the PECVD technique.
Production of carbon nanostructures for bioapplications
Keywords: Nanotubo de carbono; Nanoestrutura híbrida de carbono; Plasma; PECVD; Fonte DC-pulsada; Carbon nanotube; Hybrid carbon nanostructure; Plasma; PECVD; DC-pulsed source; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS